Development of Islamic Higher Education in Indonesia - Gumanti, Miswan; Maisaroh, Iis; Warisno, Andi; Andari, An An; Anshori, M Afif (Graduate Program Magister Manajemen Pendidikan, 2023)
This study aimed at describing the development of public and private Islamic universities in Indonesia and the renewal of the Islamic education system in Indonesia. This study is qualitative. The results obtained indicate that the development of PTAI has had a major impact on political, economic, social, cultural mobility and so on, among Muslims in Indonesia in particular and Indonesian society in general. In responding to the demands and developments of the times, within the body of IAIN itself there has been a fundamental change by updating the institution to become UIN.